Authentic Evaluation Model in Islamic Religious Education Curriculum: Assessing Values, Attitudes, and Social Practices - Asykur, Muamar; Karmala, Karmala; Swandi, Candra; Ahmad, Nurwahida; Ningsih, Yuliawati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze authentic assessment in Islamic religious education learning. This type of research is qualitative, collecting data from literature studies in the form of journals and books known as library research, which contain information about authentic assessment in Islamic religious education learning. The data analysis technique in this study was content analysis. After data analysis, the research results obtained were that authentic assessment is very important to implement in Islamic religious education learning. Authentic assessment includes several aspects of assessment, such as affective, cognitive, and psychomotor. A teacher can use attitude assessment to evaluate student behavior while learning or outside the classroom. Spiritual and social attitude competencies must be implemented in learning through habits and examples demonstrated by students in their daily lives, therefore the achievement of these attitude competencies must be assessed by the teacher continuously. In addition, authentic assessment not only assesses learning outcomes, but also assesses the learning process carried out by students to acquire knowledge and apply it in everyday life. In conclusion, authentic assessment techniques pay attention to three things: : affective, cognitive, and psychomotor competencies.